Systemic and local effects of doxycycline and low-intensity laser treatment on periodontitis in rats - Silveira, Glauco Rodrigues Carmo; de Lima, Daniela Coelho; Cintra, Luciano Tavares Angelo [UNESP]; Brigagão, Maísa Ribeiro Pereira Lima; Ervolino, Edilson [UNESP]; Fernandes, Leandro Araújo (My University, 2021)
Purpose: This study evaluated the systemic and local effects of doxycycline (DOX) and lowintensity laser (LIL) treatment as adjuvants to scaling and root planing (SRP) in the treatment of experimental periodontitis in rats. Methods: The sample consisted of 180 male rats (Rattus norvegicus albinus, Wistar), of which 30 did not receive induction of periodontal disease (negative control [NC] group) and 150 received induction of periodontal disease in the lower first molar. After 7 days, the ligature was removed, and the animals were divided into the following groups: NT (no treatment), SRP (SRP), DOX (SRP and DOX irrigation), LIL (SRP and laser irradiation), and DOX+LIL (SRP, DOX, and LIL). The animals were euthanized at 7, 15, and 30 days; thereafter, biochemical, radiographic, histological, and immunohistochemical analyses were performed. Results: In the intragroup analysis, lower concentrations of α-1-glycoprotein acid (α-1-Ga) and complement 3 (C3) were observed in the DOX+LIL group than in all other groups at all time points, as well as lower levels of complement 4 (C4) at 15 and 30 days (P<0.001). Less bone loss was observed in the DOX, LIL, and DOX+LIL groups than in the NC and SRP groups at all time points (P<0.001). There was a smaller number of tartrate-resistant acid phosphatase (TRAP)-positive cells in the DOX+LIL group than in the other groups at all time points (P<0.001). Positive correlations were observed between the systemic levels of α-1-Ga, C3, and C4 and the number of TRAP-positive cells. Conclusions: The combination of DOX with LIL as SRP adjuvants was effective both systemically and locally for the treatment of experimental periodontitis in rats.
Keywords: Doxycycline; Lasers; Periodontal disease; Periodontitis; Rats